Identification of Major and Minor Allergens of Mud Crab (Scylla Serrata) - Nurul Izzah AR; Rosmilah M; Zailatul Hani MY; Noormalin A; Faizal B; Shahnaz M (Penerbit UKM, 2015)
Crab meat is a valuable source of proteins and functional lipids and is widely consumed worldwide. However, the prevalence of crab allergy has increased over the past few years. In order to better understand crab allergy, it is necessary to identify crab allergens. The aim of the present study was to compare the IgE-binding proteins of raw and cooked extracts of mud crab (Scylla serrata). Raw and cooked extracts of the mud crab were prepared. Protein profiles and IgE reactivity patterns were identified by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) followed by immunoblotting using sera from 21 skin prick test (SPT) positive patients. In SDS-PAGE, 20 protein bands (12 to 250 kDa) were observed in the raw extract while the cooked extract demonstrated fewer bands. Protein bands between 40 to 250 kDa were sensitive to heat denaturation and no longer observed in the cooked extract. In immunoblotting experiments, raw and cooked extracts demonstrated 11 and 4 IgE-binding proteins, respectively, with molecular weights of between 23 and 250 kDa. A heat-resistant 36 kDa protein, corresponding to crab tropomyosin was identified as the major allergen of both extracts. In addition, a 41 kDa heat-sensitive protein believed to be arginine kinase was shown to be a major allergen of the raw extract. Other minor allergens were also observed at various molecular weights.